Raulí (Nothofagus alpina = N. nervosa): The Best Quality Hardwood in Patagonia - Marchelli, Paula (2021)
Nothofagus alpina (Poepp. and Endl.) Oerst. (= N. nervosa (Phil.) Dim. et Mil.), raulí, is an iconic forest tree species of the South American temperate forests due to its hardwood quality. With a pinkish colour and light red tints, raulí’s wood is very appreciated in the regional and international market for its excellent physical and mechanical characteristics. The texture is fine and homogeneous, presenting a very smooth veining with linear fibres that allow obtaining even excellent roof tiles and a density of approximately 0.55 g/cm3 at 12% moisture content. Easy to dry, once dry it is dimensionally stable, easy to saw, brush and turn, achieving excellent terminations and therefore very suitable for door and window frames, furniture and fine woodwork (Diaz-Vaz 1987). Owing to this superb wood quality, raulí has been extensively logged, mainly during the first half of the twentieth century, causing a dramatic reduction of its forests (Donoso and Lara 1995; Gonzalez Peñalba et al. 1997).